A Review Review Artikel: Formulasi Evaluasi dan Stabilitas Sediaan Tablet Atorvastatin: Formulation, Evaluation, and Stability of Atorvastatin Tablet Dosage Forms - Saputro, M. Ramadhan; Aulia, Reihan Zalza; Aisyah F, Nur Fajriyah; Isnen, M. Dzul Faqih; B, Maria Helentina; Pratama, Reza (Jurnal Medika Farmaka, 2025)
Introduction: Atorvastatin is a statin drug with low solubility and stability, resulting in limited bioavailability. This review aims to examine various formulation methods, evaluations, and stability tests of atorvastatin tablets. Methods: This study is a literature review discussing different formulation approaches and stability evaluations of atorvastatin tablets with various release systems. Articles were collected from Google Scholar, ScienceDirect, and ResearchGate, then analyzed based on formulation methods, stabilizing excipients, and stability testing techniques. Results: The use of dry granulation with basic excipients, sustained release and extended release systems, as well as cocrystal formation with coformers such as nicotinamide and ascorbic acid, effectively improved the solubility, stability, and bioavailability of atorvastatin. Conclusion: The combination of appropriate formulation strategies and optimized dosage design is key to developing atorvastatin tablets that are stable and therapeutically effective.